Out of the Loop, in Your Bubble: Mind Wandering Is Independent From Automation Reliability, but Influences Task Engagement - Gouraud, Jonas; Delorme, Arnaud; Berberian, Bruno (Frontiers in Human Neuroscience, 2018)
This study examined the influence of automation reliability on task-unrelated mind wandering frequency and the impact of mind wandering on task engagement. Automated environment features make it particularly prone to increase mind wandering frequency. Through mechanisms like complacency or agency, automating a task could increase mind wandering frequency for the operator. For safety-critical industries, the lower perception and degraded stimuli processing associated with mind wandering, summarized by the term “decoupling hypothesis”, are particularly concerning. 16 participants supervised an autopilot avoiding obstacles with two levels of reliability. Each condition lasted 45 minutes. We recorded thoughts as either pertaining to being focused, task-related mind wandering or task-unrelated mind wandering. We also recorded perceived mental demand, trust regarding the autopilot and oculometric measures. Based on questionnaire results, our protocol succeeded in inducing more mental demand and lower trust when the automation was unreliable. Attentional states were not correlated, nor did it influence trust in the system reliability. On the contrary, mental demand ratings and pupil diameter were lower during both task-related and task-unrelated mind wandering, compared to those during the focus attentional state. This shows that perceptual decoupling also affects the engagement of operators in automated environments, which may dramatically lower their ability to supervise automation efficiently. This research informs human-automation designers to consider operator engagement when creating automated systems.